Analisis Validitas dan Efektivitas E-LKPD Berbasis Virtual Laboratorium Terintegrasi STEM pada Submateri Zat Makanan untuk Melatihkan Keterampilan Literasi Sains Peserta Didik Kelas XI SMA - Putri, Dien Amelia Defani Ananda; Pramita Yakub (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the validity and effectiveness of E-LKPD (Electronic Student Worksheets) based on a virtual laboratory integrated with STEM for the subtopic of nutrients in developing the science literacy skills of 11th-grade high school students. This study is a research and development (R&D) study using the 4D model. The test subjects in this study were 20 11th-grade students at SMAN 2 Sidoarjo. The validity of the E-LKPD was determined through an assessment by two expert validators covering the aspects of presentation appropriateness, content appropriateness, and linguistic appropriateness, while effectiveness was measured through science literacy tests in the form of pre-tests and post-tests, which were analyzed using the N-gain score. The results showed that the E-LKPD based on a virtual laboratory integrated with STEM was deemed highly valid, with an average percentage of 90%, as assessed in terms of presentation appropriateness, content appropriateness, and linguistic appropriateness. Furthermore, the E-LKPD was found to be effective in developing students’ science literacy skills, as evidenced by an increase in the N-gain score of 0.74, which falls into the “high” category. Based on these results, it can be concluded that the E-LKPD based on an integrated STEM virtual laboratory for the subtopic of nutrients is appropriate and effective for use as instructional material to develop the science literacy skills of 11th-grade high school students.